The relationship between futile medical care and respect for patient dignity: a cross-sectional study - Faezeh Nazari; Maryam Chegeni; Parvin Mongolian Shahrbabaki (BMC, 2022)
Abstract Background Various technologies and interventions at intensive care units can lead to futile medical care for critically ill patients. Futile medical care increases patients' suffering and costs, reduces nurses' attention to patients, and thus affects patients' dignity. This study aimed to investigate the relationship between futile medical care and respect for patient dignity from the perspective of nurses working in intensive care units of medical centers. Methods We conducted this cross-sectional study on 160 nurses working in intensive care units in Kerman. We measured nurses' perceptions of futile care and respect for patient dignity using futile care and patients' dignity questionnaire. We used linear regression model to investigate the effect of futile care on the patient dignity. Results The mean severity and frequency of futile care in the intensive care unit were 57.2 ± 14.3 and 54.1 ± 19, respectively. Respect for patient privacy and respectful communication were desirable, while patients' autonomy was not desirable. We found a significant direct relationship (p = 0.006) between the severity of futile care and respect for patient dignity, with every unit increase in futile care, a 0.01 unit increase was available in patient dignity. We observed no significant association between frequency of futile care and dignity. Conclusion Our results indicated the effect of futile care on nurses' respect for patient dignity. Nurses must raise their awareness through participating in training classes and specialized workshops to improve the level of care, the quality of care, and respect for patient dignity.